2019
DOI: 10.1002/mdc3.12742
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Huntington's Disease like 2 and Huntington's Disease Clinical Phenotypes

Abstract: Background Huntington's disease like 2 (HDL2) is the most common Huntington's disease (HD) phenocopy in many countries and described as the phenocopy with the greatest resemblance to HD. The current clinical description of HDL2 is based on retrospective data. It is unknown whether HDL2 has clinical features that distinguish it from HD. Objective To describe the HDL2 phenotype and compare it to HD systematically. Methods A blinded cross‐sectional design was used to compare the HDL2 (n = 15) and HD (n = 13) phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Inherited defects in JPH3 were the first junctophilin gene disorder associated with a human disease, namely Huntington Disease-Like 2 (HDL2) ( 17 ). Like Huntington Disease, HDL2 usually presents in adulthood (during the fourth decade of life) with a relentless progressive triad of movement, psychiatric, and cognitive abnormalities, which lead to death within 10 to 20 yr ( 218 ). HDL2 is clinically indistinguishable from Huntington Disease.…”
Section: Inherited Diseases Caused By Junctophilin Gene Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inherited defects in JPH3 were the first junctophilin gene disorder associated with a human disease, namely Huntington Disease-Like 2 (HDL2) ( 17 ). Like Huntington Disease, HDL2 usually presents in adulthood (during the fourth decade of life) with a relentless progressive triad of movement, psychiatric, and cognitive abnormalities, which lead to death within 10 to 20 yr ( 218 ). HDL2 is clinically indistinguishable from Huntington Disease.…”
Section: Inherited Diseases Caused By Junctophilin Gene Variantsmentioning
confidence: 99%
“…In addition, HDL2 patients show movement disorders including eye motion abnormalities, increased Parkinsonism, chorea, hypokinesia (rigidity, bradykinesia), dysarthria, and hyperreflexia in the later stages of the disease. There is a strong correlation between the disease duration and progression of the motor and cognitive disorder ( 218 ). Dementia is a universal feature of HDL2.…”
Section: Inherited Diseases Caused By Junctophilin Gene Variantsmentioning
confidence: 99%
“…Relatively early orolingual involvement with dysarthria, dysphagia or choking in patients with cognitive problems or hyperkinetic limb movements appears suggestive of HD. This may in part be due to the composition of our cohort, since a recent study showed that dystonia and dysarthria were more common in HDL2 than HD patients, although associations were not analysed 48 . Furthermore, different types of dysarthria in HD have been shown to vary significantly in terms of general motor dysfunction 49 .…”
Section: Discussionmentioning
confidence: 99%
“…HDL‐2 is caused by a CTG/CAG trinucleotide repeat expansion located within the junctophilin 3 (JPH3) gene, with expansions over 41 repeats causing disease. The age of onset is inversely related to the number of repeats, similar to HD, but anticipation has not been demonstrated; and imaging findings are similar to HD 3,4 . Junctophilin‐3 appears to be involved in calcium regulation and junctional membrane structures.…”
Section: Disorders Of Red Blood Cellsmentioning
confidence: 98%
“…Parkinsonism and dystonia occur more frequently than in Huntington's disease (HD), and eye movements are normal or only mildly hypometric. Behavioral or psychiatric manifestations can be the presenting symptom 3,4 . Ten percent of patients have acanthocytes, however the etiology of this is unknown.…”
Section: Disorders Of Red Blood Cellsmentioning
confidence: 99%